Develop Hybrid Native and Mobile Web Apps. IN ASP.NET MVC 3. - Church, Shane (MSDN magazine)
Shane Church shows you how to build a mobile Web application with ASP.NET MVC 3 and take advantage of native mobile features such as the camera and accelerometer.